Relationship between migraine and sleep disorders in adolescents - Lina Waty; Supriatmo Supriatmo; Bistok Saing (Paediatrica Indonesiana, 2013)
Background Headaches and sleep disorders may influenceacademic performances, personality, memory, and interpersonalrelationships. Migraine is the most common headache type seen inadolescents. Although headaches and sleep disorders are believedto be related, there has been little study in this area.Objectives To assess the relationship between migraine andsleep disorders in adolescents and compare different types ofsleep disorders found in adolescents with migraine vs. healthyadolescents.Methods We conducted a cross sectional study in December 2009on students of three junior high schools in the Secanggang District,Langkat Regency, North Sumatera. We included adolescents aged12 to 17 years who suffered from migraines, as defined by theInternational Cftissificaticm of Headache Disorders, 2nd edition criteria(ICHD-II), and h ealthy adolescents who did not experien cemigraines as the control group. Parents filled questionnaires ontheir child's sleep patterns for one week.Results A total of 100 adolescents were enrolled in the study,consisted of 50 adolescents in the migraine group and the others50 in the control group. There was a significant difference in theincidence of sleep disorders between the two groups (76% and30%, in the case and control groups, respectively; P= 0.0001).Moreover, significant differences were also found in the prevalenceof different sleeping disorder types between the case and controlgroups, i.e. insomnia (62% and 30%, respectively; P= 0.003), sleepapnea (56% and 16%, respectively; P= 0.0001), restlessness (56%and 18%, respectively; P= 0.0001) , parasomnia (76% and 10%,respectively; P= 0.0001), narcolepsy (42% and 16%, respectively;P= 0.008), and excessive daytime sleepiness (50% and 26%,respectively; P= 0.023).Conclusions Migraine in adolescents is significantly associatedwith sleep disorders. Parasomnia is the most common type ofsleeping disorder observed in adolescents with migraines in ourstudy.